Testing the new Keynesian Phillips curve without assuming identification - Sophocles Mavroeidis (Brown University, Department of Economics, 2006)
We re-examine the evidence on the new Phillips curve model of Gali and Gertler (Journal of Monetary Economics 1999) using the conditional score test of Kleibergen (Econometrica 2005), which is robust to weak identification. In contrast to earlier studies, we find that US postwar data are consistent both with the view that inflation dynamics are forward-looking, and with the opposite view that they are predominantly backward-looking. Moreover, the labor share does not appear to be a relevant determinant of inflation. We show that this is an important factor contributing to the weak identification of the Phillips curve.
Keywords: C22; E31; 330; Weak instruments; Rational Expectations; GMM; robust inference; New-Keynesian Phillips Curve; Rationale Erwartung; Inflation; Momentenmethode